The Role of Information Systems and Quality Control in Reducing Defective Products - Erdiansyah Gama Saputra, Imam Bustan; Purwadhi, Purwadhi; Agung , Wiseto P. (Devotion : Journal of Research and Community Service, 2025)
Negative inventory continues to be a recurring issue in pharmacy operations, particularly when discrepancies arise between physical stock and system records. Such inconsistencies lead to service errors, cost inefficiencies, and inaccurate inventory reporting. The implementation of information technology (IT) systems is considered a solution that improves recording processes, enhances data integration, and increases transaction transparency. However, the effectiveness of IT systems is influenced by the presence of adequate quality control mechanisms that ensure the consistency of operational procedures. This study examines the effect of IT systems on quality control and negative inventory, as well as the mediating role of quality control at Fupha Pharmacy Banyumas. Using a quantitative explanatory approach with 30 respondents involved in inventory and operational management, the findings demonstrate that IT systems significantly improve quality control and reduce negative inventory. Furthermore, quality control mediates the effect of IT systems on inventory discrepancies. These results highlight the importance of integrating technology and procedural supervision to achieve higher inventory accuracy in the pharmaceutical sector.